2023
DOI: 10.1037/fsh0000707
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pediatric behavioral health in primary care in rural and urban clinics.

Abstract: Introduction:The prevalence of behavioral health disorders in children is approximately 15%-20%, yet less than half of the children ever receive treatment for these conditions. The lack of access to behavioral health care is common in urban areas but even more difficult to access in rural areas. Screening for behavioral health in a primary care setting is one of the first strategies to reduce this problem and improve access to care. The primary goal of this study was to examine behavioral health screening prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The finding that over 40% and almost 20% of patients were accessing AH professionals and support services, respectively, confirms they are a critical component of paediatric care and should be included in any integrated health care models. Integration and colocation of paediatric services can also decrease travel time for patients, improve access to care and reduce the stigma rural patients have reported when accessing mental health or social support services 19 . The latter is an important consideration as carers and patients from rural communities have indicated that a barrier to accessing services is a fear they may be recognised 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that over 40% and almost 20% of patients were accessing AH professionals and support services, respectively, confirms they are a critical component of paediatric care and should be included in any integrated health care models. Integration and colocation of paediatric services can also decrease travel time for patients, improve access to care and reduce the stigma rural patients have reported when accessing mental health or social support services 19 . The latter is an important consideration as carers and patients from rural communities have indicated that a barrier to accessing services is a fear they may be recognised 20 …”
Section: Discussionmentioning
confidence: 99%
“…Integration and colocation of paediatric services can also decrease travel time for patients, improve access to care and reduce the stigma rural patients have reported when accessing mental health or social support services. 19 The latter is an important consideration as carers and patients from rural communities have indicated that a barrier to accessing services is a fear they may be recognised. 20 Moreover, the percentage of patients who were accessing or referred to an AH professional is higher than in previous studies, with a recent study reporting 11.2% of patients were referred to an AH service.…”
Section: Discussionmentioning
confidence: 99%